2017
DOI: 10.1038/s41598-017-05162-x
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer stem cells manifest radioresistance: Association with upregulated AP-1 activity

Abstract: Transcription factor AP-1 plays a central role in HPV-mediated cervical carcinogenesis. AP-1 has also been implicated in chemo-radio-resistance but the mechanism(s) remained unexplored. In the present study, cervical cancer stem-like cells (CaCxSLCs) isolated and enriched from cervical cancer cell lines SiHa and C33a demonstrated an elevated AP-1 DNA-binding activity in comparison to non-stem cervical cancer cells. Upon UV-irradiation, CaCxSLCs showed a UV exposure duration-dependent higher proliferation and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 70 publications
2
34
0
Order By: Relevance
“…Recent studies have reported that cells with CSC properties could be isolated from HPV-positive and HPV-negative cervical cancer cells by triple gating with the following sequence: (i) isolating the side population, (ii) gating the CD49f þ /CD71 À population, and (iii) gating the CD133 þ population. The cells in the isolated population with triple gating [SP -> (CD49f þ CD71 À )-> CD133 þ ] formed more cervicospheres than those in the [NSP-> (CD49f À CD71 þ )-> CD133 À ] population, suggesting that the former population displayed CSC properties (30). In addition, neither the side population (SP) nor the nonside population (NSP) isolated from HPV-negative C33A cells could form cervicospheres (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have reported that cells with CSC properties could be isolated from HPV-positive and HPV-negative cervical cancer cells by triple gating with the following sequence: (i) isolating the side population, (ii) gating the CD49f þ /CD71 À population, and (iii) gating the CD133 þ population. The cells in the isolated population with triple gating [SP -> (CD49f þ CD71 À )-> CD133 þ ] formed more cervicospheres than those in the [NSP-> (CD49f À CD71 þ )-> CD133 À ] population, suggesting that the former population displayed CSC properties (30). In addition, neither the side population (SP) nor the nonside population (NSP) isolated from HPV-negative C33A cells could form cervicospheres (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…The cells in the isolated population with triple gating [SP -> (CD49f þ CD71 À )-> CD133 þ ] formed more cervicospheres than those in the [NSP-> (CD49f À CD71 þ )-> CD133 À ] population, suggesting that the former population displayed CSC properties (30). In addition, neither the side population (SP) nor the nonside population (NSP) isolated from HPV-negative C33A cells could form cervicospheres (30,31). These results imply that HPV infection is an important factor in the initiation of CSC characteristics in cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SPs are not exclusive to SCs and is not universal in all cancer types . As opposed to the studies using expression of a single functional marker, recent studies have demonstrated the use of “sequential gating and intermittent of CCSCs,” which helps in high yield of CSCs . Methods like optical imaging of CCSCs can be useful to monitor CCSC real time, in vitro and in vivo.…”
Section: Discovery Of Ccscs and Their Identification Using Functionalmentioning
confidence: 99%
“…Different from clinical performance and molecular typing used in the NCCN Guidelines, a treatment‐related gene signature is developed to directly predict the responsiveness to a specific treatment. Due to the overlapping mechanisms of RT and chemotherapy resistance, previous signatures centred on a single treatment are not dedicated to distinguishing between the different beneficiaries of RT and chemotherapy. Faced with this situation, we hope to establish new indicators to guide patient stratification and provide guidance for the use of RT and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%